Adaptive Superamphiphilic Organohydrogels with Reconfigurable Surface Topography for Programming Unidirectional Liquid Transport. (1st March 2019) - Zhao, Ziguang; Li, Chuxin; Dong, Zhichao; Yang, Yingchao; Zhang, Longhao; Zhuo, Shuyun; Zhou, Xintao; Xu, Yichao; Jiang, Lei; Liu, Mingjie
Abstract: Adaptive materials with reconfigurable surface topography in response to external environments have attracted considerable attention in various fields. Here, adaptive superamphiphilic organohydrogels with reconfigurable surface topography are reported, featuring a high degree of freedom. The organohydrogels can simultaneously adapt to different surrounding mediums and reversibly switch between hydrogel‐ and organogel‐dominated surface reconfigurations to realize adaptive superhydrophilic and superoleophilic transitions. Meanwhile, these adaptive organohydrogels possess a heteronetwork complementary effect to elicit surface self‐healing capacity. Importantly, owing to these organohydrogels' reversible wettability transition, excellent surface morphing performance and bioinspired strategy, various geometrically complex biomimetic topographies can be programmed, offering unique unidirectional transport for opposite‐featured liquids in multimedia environments. Smart organohydrogel‐based microfluidic devices are also developed for on‐demand remote programming of liquid transport. Therefore, the organohydrogels suggest a reconfigurable surface topography design strategy, and would act as adaptive programmable materials for smart surface applications. Abstract : Adaptive organohydrogel materials synergistically produce reconfigurable surface topography featuring a high degree of freedom. The organohydrogels can reversibly switch between hydrogel‐ and organogel‐dominated surface reconfigurations in different surrounding mediums. Importantly, by the integration of the reversible superamphiphilic transition, excellent surface morphing performance, and bioinspired strategy, the adaptive organohydrogel materials realize unique unidirectional transport for opposite‐featured liquids in multimedia environments.